2016
DOI: 10.1016/j.jclinepi.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of quality of thyroid-specific health-related quality-of-life instruments recommends ThyPRO for patients with benign thyroid diseases

Abstract: The ThyPRO is recommended for the assessment of HRQOL in patients with benign thyroid diseases while measurement properties of GO-QOL and ThyTSQ are satisfactory in measuring HRQOL of patients with Graves' ophthalmopathy and hypothyroidism, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 49 publications
1
63
0
1
Order By: Relevance
“…15 The ThyPRO and other instruments were administered in English, French, German, or Dutch as appropriate. We had initially planned for cardiovascular events and thyroid-specific quality of life to be the two primary outcomes.…”
Section: Procedures and Outcomesmentioning
confidence: 99%
“…15 The ThyPRO and other instruments were administered in English, French, German, or Dutch as appropriate. We had initially planned for cardiovascular events and thyroid-specific quality of life to be the two primary outcomes.…”
Section: Procedures and Outcomesmentioning
confidence: 99%
“…Some questionnaires assess general measures, while others assess measures that are specific to particular diseases, such as thyroid disease. Several questionnaires specific to thyroid disorders were recently evaluated and four related to hypothyroidism and benign thyroid disease were studied (2). The highest quality instruments for assessing symptoms in patients with hypothyroidism were found, in this recent metaanalysis (2), to be the Thyroid-Specific Patient-Reported Outcomes Measure (ThyPRO) (3, 4) and Thyroid Treatment Satisfaction Questionnaire (5, 6).…”
Section: Patient-reported Outcomes During Levothyroxine Therapymentioning
confidence: 99%
“…The ThyPRO is a thyroid-related QoL instrument, which has been validated in patients with thyroid disease and identified as being more sensitive than the less specific measure, SF-36. [11][12][13][14] Adult patients undergoing thyroidectomy for benign thyroid disease have been reported to have significantly improved QoL, after their surgery, as measured by the ThyPRO questionnaire. 15 Similarly, QoL following surgery was also reported to improve for those with GD.…”
mentioning
confidence: 95%
“…However, these authors suggested that the questionnaire used (SF‐36) may not have been the most appropriate instrument to detect a difference in QoL between the different treatment modalities, and did not clarify which therapeutic option is associated with the best QoL. The ThyPRO is a thyroid‐related QoL instrument, which has been validated in patients with thyroid disease and identified as being more sensitive than the less specific measure, SF‐36 . Adult patients undergoing thyroidectomy for benign thyroid disease have been reported to have significantly improved QoL, after their surgery, as measured by the ThyPRO questionnaire .…”
Section: Introductionmentioning
confidence: 99%